Declarative memory profiles in children with non-specific intellectual disability: a cluster analysis approach - Sajewicz-Radtke, Urszula; Łada-Maśko, Ariadna; Olech, Michał; Leoniak, Krzysztof J.; Radtke, Bartosz M. (Frontiers in Psychiatry, 2025)
IntroductionIntellectual disability (ID) is increasingly being understood as a multidimensional condition that requires assessment beyond general intelligence. While traditional approaches focus on IQ, memory impairment plays a critical role in learning and adaptation. This study explored the declarative memory profiles of individuals diagnosed with non-specific intellectual disability (NSID) to identify cognitive patterns that may inform intervention strategies.MethodsThe study included 114 individuals (56 girls and 58 boys) aged 10–17 years with a confirmed mild NSID diagnosis. The participants underwent a comprehensive declarative memory assessment using the Polish version of the Test of Memory and Learning, Second Edition (TOMAL-2). A subset of 68 participants was assessed using the Stanford-Binet Intelligence Scales, Fifth Edition (SB5). Cluster analyses were performed to identify memory profiles based on the TOMAL-2 indices and their relationships with intelligence measures.ResultsTwo distinct memory profiles were identified. Cluster 1 (53% of the sample) exhibited lower scores across all memory indices, particularly for free recall, associative recall, and learning efficiency. Cluster 2 (47%) demonstrated relatively preserved memory abilities. Further analysis incorporating IQ measures showed that nonverbal intelligence was more strongly associated with memory performance than verbal intelligence. Notably, learning efficiency, rather than delayed verbal recall, was the strongest differentiator between the clusters.ConclusionsThese findings highlight the heterogeneity of memory abilities in NSID, emphasizing the need for cognitive profiling beyond IQ. Learning potential may be a more predictive factor of functional outcomes, warranting further research and targeted interventions to enhance the adaptive capabilities in this population.